2018
DOI: 10.1007/s10964-018-0819-4
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Perspective on the Relationships between Emotional Separation, Parental Trust, and Identity in Adolescents

Abstract: Emotional separation and parental trust in parent-adolescent relationships are important factors for adolescent identity formation. However, prior research findings on emotional separation are inconsistent. This study aimed to conduct a more rigorous examination of the associations of emotional separation and parental trust with identity synthesis, confusion, and consolidation by applying a bi-factor model to identity, using adolescent samples from Lithuania (N = 610; 53.9% female; M = 14.92), Italy (N = 411; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 52 publications
6
30
0
Order By: Relevance
“…These results indicated that the DFAe of the present data reflected the non-random temporal structure of the phase. values are similar to those reported in previous studies 32,33,47,48 .…”
Section: Surrogated Data Analysis Was Conducted In Order To Confirm Wsupporting
confidence: 92%
See 1 more Smart Citation
“…These results indicated that the DFAe of the present data reflected the non-random temporal structure of the phase. values are similar to those reported in previous studies 32,33,47,48 .…”
Section: Surrogated Data Analysis Was Conducted In Order To Confirm Wsupporting
confidence: 92%
“…This subjective experience of identity consists of two fundamental components: identity synthesis and identity confusion. Identity synthesis is a feeling that one's self is temporally continuous and consistent and one knows where one is headed (e.g., a sense of knowing their purpose and direction), while identity confusion refers to a feeling of one's self as temporally changeable and fragmented, and one is indecisive and unable to keep commitments to important life decisions (e.g., a sense of feeling mixed up) [30][31][32][33] . Identity synthesis and confusion are not polar opposites but exist simultaneously 31 .…”
Section: Introductionmentioning
confidence: 99%
“…The rank correlation between identity synthesis and confusion was rho = − 0.56 (p < 0.001, 95% CI = − 0.70, − 0.37). The Cronbach's alphas for the present data (N = 68) were 0.80 for synthesis and 0.68 for confusion; these values are similar to those reported in previous studies 32,33,47,48 .…”
Section: Lrtcsupporting
confidence: 91%
“…Identity synthesis is a feeling that one's self is temporally continuous and consistent and one knows where one is headed (e.g., a sense of knowing their purpose and direction), while identity confusion refers to a feeling of one's self as temporally changeable and fragmented, and one is indecisive and unable to keep commitments to important life decisions (e.g., a sense of feeling mixed up) [30][31][32][33] . Identity synthesis and confusion are not polar opposites but exist simultaneously 31 .…”
mentioning
confidence: 99%
“…We also based the system on the need to develop a motivational profile in the professional development of teachers (Guzmán, 2019), data of the impact of moral actions on the intensification of moral growth (Yao, 2018), and theories of adult education, which are appropriate for students aged 18-21. We assimilated the ideas of modern scholars about the importance of consolidating identity between parents and children (Sugimura, 2018), significance of parental influence in order to prevent negative behavior (Nqweni et al, 2010).…”
Section: Methodsmentioning
confidence: 99%